2005
DOI: 10.1176/appi.ajp.162.9.1706
|View full text |Cite
|
Sign up to set email alerts
|

Subgenual Prefrontal Cortex Volumes in Major Depressive Disorder and Schizophrenia: Diagnostic Specificity and Prognostic Implications

Abstract: These findings add to the evidence that abnormalities in the subgenual region of the anterior cingulate play a role in at least some types of mood disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
3
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 43 publications
7
82
3
6
Order By: Relevance
“…In contrast to Bremner et al (2002) and Pizzagalli et al (2004), who found no differences in BA25 or in BA32 (Bremner et al, 2002) volume between MDD patients and healthy controls, Coryell et al (2005) subsequently reported a reduction in left subcallosal gyrus volume in patients with MDD relative to controls. Finally, a number of studies demonstrate smaller gray (Lavretsky et al, 2007;Caetano et al, 2006;Ballmaier et al, 2004) and white (Ballmaier et al, 2004) matter volume in 'total' and in ventral (Tang et al, 2007) ACC in patients with MDD relative to controls; however, the cingulate regions assayed in these studies varied widely.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In contrast to Bremner et al (2002) and Pizzagalli et al (2004), who found no differences in BA25 or in BA32 (Bremner et al, 2002) volume between MDD patients and healthy controls, Coryell et al (2005) subsequently reported a reduction in left subcallosal gyrus volume in patients with MDD relative to controls. Finally, a number of studies demonstrate smaller gray (Lavretsky et al, 2007;Caetano et al, 2006;Ballmaier et al, 2004) and white (Ballmaier et al, 2004) matter volume in 'total' and in ventral (Tang et al, 2007) ACC in patients with MDD relative to controls; however, the cingulate regions assayed in these studies varied widely.…”
Section: Introductionmentioning
confidence: 73%
“…Two studies have demonstrated a positive relation between ACC volume and treatment response in MDD (Coryell et al, 2005;Chen et al, 2007), although an earlier study was negative in this respect (Drevets et al, 1997). PET and functional MRI studies show that treatment with antidepressants is associated with increased cerebral metabolism (Vlassenko et al, 2004) and greater activation in the ACC in patients with MDD (Chen et al, 2007;Davidson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9, 3032 The subgenual ACC is considered a more archaic region than the rostral ACC; has extensive connections with other parts of the brain such as the amygdala, raphe nuclei, and brain stem autonomic nuclei; and is involved in emotional processing, monoaminergic neurotransmitter release, and autonomic regulation. 33 While abnormal function has been found in both the rostral and the subgenual ACC in major depression, only the subgenual ACC has been associated with a reduction in volume, 31,34 and this may represent the core abnormality of treatment resistant depression. 35 Although elevated activity in the rostral ACC has been shown to predict response to pharmacological treatment, 9,10 response to antidepressant treatment has been shown to be primarily mediated by the subgenual ACC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Mayberg et al (2005) showed the SCC to be hyperactive in TRD patients, whereas previous literature has not reported the SCC to be hyperactive in non-TRD patients. In addition, studies evaluating brain structure using MRI have shown abnormalities in frontal regions and the cingulate gyrus, specifically, reduced volume and gray matter thickness in these areas in patients with MDD and bipolar disorder (Coryell et al, 2005;Lyoo et al, 2004;Nugent et al, 2006). These regions are thought to be part of a limbic-cortical-striatalpallidal-thalamic network that is involved in emotion processing (Anderson et al, 2012;Nugent et al, 2006).…”
Section: Introductionmentioning
confidence: 99%